2006
DOI: 10.1093/eurheartj/ehi825
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and lifetime risk of atrial fibrillation: the Rotterdam study

Abstract: In this prospective study in a European population, the prevalence and incidence of AF increased with age and were higher in men than in women. The high lifetime risk to develop AF was similar to North American epidemiological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

64
954
27
98

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,664 publications
(1,181 citation statements)
references
References 36 publications
64
954
27
98
Order By: Relevance
“…The prevalence of AF estimated in our study is somewhat higher than the estimates derived from the considerably older, population-based Rotterdam Study which was conducted between 1990 and 1999 (19). In this study, the prevalence of AF was 4.0% in the age-group 65-69 years (5.1% in our study) and similarly showed a marked increase with age.…”
Section: Discussioncontrasting
confidence: 72%
“…The prevalence of AF estimated in our study is somewhat higher than the estimates derived from the considerably older, population-based Rotterdam Study which was conducted between 1990 and 1999 (19). In this study, the prevalence of AF was 4.0% in the age-group 65-69 years (5.1% in our study) and similarly showed a marked increase with age.…”
Section: Discussioncontrasting
confidence: 72%
“…The lifetime risk is 1 in 4 according to previous studies,2, 3 and more than 1 in 3 based on recent data 4. Several risk factors have been identified, many of which are also risk factors for several types of cancer, such as age, smoking, alcohol consumption, and obesity 5, 6.…”
Section: Introductionmentioning
confidence: 96%
“…Prevalence of AF sharply increases with age, and with our rapidly aging population, prevalence of AF is expected to double by 2060 2, 3. Cardioembolic stroke is one of the most common complications of AF, and at least 1 in 3 strokes is directly attributable to AF 4, 5.…”
Section: Introductionmentioning
confidence: 99%